Catalyst-Free Synthesis of Hollow-Sphere-Like ZnO and Its Photoluminescence Property - Junye Cheng; Xiuying Yang; Hua Tian; Bin Zhao; Deqing Zhang (Advances in Materials Science and Engineering)
Hollow-sphere-like ZnO was successfully prepared by a facile combustion route at 950°C, and no external catalysts or additives were introduced. The morphology and structure of the hollow-sphere-like ZnO were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HRTEM), and energy dispersive spectrometer (EDS). The possible growth mechanism was discussed in detail. In addition, the as-obtained hollow-sphere-like ZnO exhibited a strong green emission at 518 nm and a weak UV emission at 385 nm. We believe that the hollow-sphere-like ZnO material may be a good candidate for application in optical devices and catalyst systems.